1989
DOI: 10.1088/0953-8984/1/7/014
|View full text |Cite
|
Sign up to set email alerts
|

Field dependence of the hyperfine splitting of holmium in holmium hydroxide

Abstract: The hyperfine splitting of 1 6 5 H ~ in holmium hydroxide has been studied by spinecho NMR at liquid-helium temperatures in fields up to 8 T. The behaviour of the dipolar splitting in fields below 0.5 T confirms that the hyperfine parameters are not thermally averaged and that the NMR signals arise solely from ions in the electronic ground state. The field dependence of the hyperfine splitting is not accurately described by crystal-field parameters derived from magnetic susceptibility measurements on Ho(OH),, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The theory of the hyperfine splitting in rare-earth compounds is described in detail in McCausland and Makenzie (1979), Bunbury et al (1989) and Li et al (1996) whose notation we shall follow. The hyperfine splitting of the electronic states is described to first order by the effective nuclear spin Hamiltonian where I is the nuclear spin, t a a t and t P are respectively the dipolar and the quadrupolar hyperfine parameters.…”
Section: The Hyperfine Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of the hyperfine splitting in rare-earth compounds is described in detail in McCausland and Makenzie (1979), Bunbury et al (1989) and Li et al (1996) whose notation we shall follow. The hyperfine splitting of the electronic states is described to first order by the effective nuclear spin Hamiltonian where I is the nuclear spin, t a a t and t P are respectively the dipolar and the quadrupolar hyperfine parameters.…”
Section: The Hyperfine Splittingmentioning
confidence: 99%
“…Preliminary computations have shown that in the exchange dominated RFe 2 compounds second order contributions to the hyperfine parameters are at most 0.05%. Therefore, the second order terms (Bunbury et al 1989) have been neglected in the present work. Because of the strong hyperfine coupling in Ho 3+ , Tb 3+ and Tm 3+ the total dipolar hyperfine constant is dominated by the dipolar intraionic term + + B B B can be regarded as independent of the applied field.…”
Section: The Hyperfine Splittingmentioning
confidence: 99%
“…The theory for the hyperfine interaction of rare-earth ions in solids is described in detail by McCausland and Mackenzie (1979). See also Dormann (1991) and Bunbury et al (1989Bunbury et al ( , 1995. In sections 2.2 and 2.3 below, we review the main points of the theory which are relevant to the present work.…”
Section: Theorymentioning
confidence: 99%
“…The free-ion hyperfine coupling constants a 0 and P 0 , together with other relevant constants pertaining to the Tb 3+ ion and the 159 Tb nucleus, are given in appendix A. Explicit expressions for the second-order terms can be found in Bunbury et al (1989). The term in I 3 z in H N arises not from the octupolar moment of the nucleus, which is negligible, but from cross-terms between the dipolar and quadrupolar terms in second-order perturbation theory.…”
Section: The Hyperfine Splittingmentioning
confidence: 99%
See 1 more Smart Citation